POLA KOMUNIKASI SUAMI ISTRI YANG TIDAK HARMONIS DI GRIYA KENARI KUBANG JAYA SIAK HULU KAMPAR - Salim, Ermairel (Ensiklopedia Sosial Review, 2020)
This research was conducted at the Griya Walnut Village Siak Hulu Riau Kampar Communication entitled Patterns of husband and wife are not Harmonious At Griya Kenari Jaya Siak Hulu Kampar Kubang. This study aims to determine the Communications Patterns husband and wife are not Harmonious At Griya Kenari Jaya Siak Hulu Kampar Kubang. Research benefits expected to be useful both theoretical and practical aspects. Theoretically, this research may be useful for the development of science communication, providing information and contributing communication patterns. Practically, this research is expected to be useful as information for individuals in developing communication patterns husband and wife in a family. In this study used qualitative methods with the intention of digging Communication Patterns of husband and wife are not Harmonious At Griya Kenari Jaya Siak Hulu Kampar Kubang. As for the time of the conduct of this study started from March 2018 to June 2018. Data collection technique is by interview, observation and documentation. Data analysis techniques to the analysis of qualitative data. From the results showed that some family communication patterns that are not in harmony occurs less effective and less fun. This happens because the habit of speaking unfriendly and irritable and grumpy. The habit of talking shout, scold and rage will make married life becomes harmonious. Seoseorang good communication in public, also does not guarantee that a person can communicate well with his family. May talk in front of other people with good communication patterns. As communication patterns by using Hp, too. Often a person communicates with the communication media does not correspond to the truth.